Overview of Blood Lead Levels in Refueling Operator Workers on Veteran Street Surakarta Based on Health Complaints - Santika Fatimah Zahro; Purwati Purwati (Indonesian Journal of Global Health Research, 2023)
Lead is a heavy metal that is naturally available in nature. As technology develops, many people use lead in various fields, thereby increasing the presence of lead in the environment, one of the uses of lead is in fuel. If humans are exposed to lead continuously, it will accumulate and cause health problems. One job that is vulnerable to lead exposure is fuel filling operators. The aim of this study was to measure the amount of lead in the blood of fueling operators and observe health problems that arise. Descriptive research method describes a particular observation that occurred. Researchers collect information on various events and observations to use as a starting point for analysis. Sampling used the quota sampling technique, namely determining the sample size from the population of refueling workers by looking at the specified criteria and the number of samples taken was 10 probands. Analysis of lead levels in the blood uses an atomic absorption spectrophotometer and the results in the form of lead levels in the blood are analyzed descriptively and presented in table form and narrated by looking at the results of the questionnaire that has been obtained. The results obtained were that the lowest level of lead in the blood of a gas station operator was 0.04 µg/dL and the highest lead level was 1.35 µg/dL. Description of blood lead levels of fuel operators on Jalan Veteran Surakarta do not exceed the limit, namely less than 10 µg/dL according to the Center for Disease Control and Prevention (CDC), with the most frequently felt symptom being work fatigue.